Pirólise dos sabões derivados dos óleos da polpa de macaúba e de crambe para a obtenção de bio-óleo - Jhon Jairo Melchor Moncada (2016)
Pyrolysis of vegetable oils is an alternative method to obtain renewable fuels and chemicals, free of nitrogen and sulphur. However, these pyrolysis liquid products or bio-oils are a complex mixture of hydrocarbons, aromatics and oxygenated compounds undesirable for fuel. In this work, were chosen as raw material macauba pulp and crambe oils, due their high productive and few studies in this field. The objective of this work was to study the fast pyrolysis of sodium, magnesium, and barium soaps obtained from macaúba pulp (high and low acidity) and crambe oils by production of bio-oil, checking yields and evaluating their potential for use as alternative fuels. First, oils were characterized by physico-chemical properties and chemical composition. Subsequently, these were saponified with NaOH for preparing sodium and magnesium soaps, and KOH for the barium and magnesium, followed by its precipitation as sodium soaps, magnesium and barium, separated from glycerol. Then it was submitted to fast pyrolysis at 550 ºC. The yield obtained was between 35 to 54% bio-oil. The major compounds were a series of hydrocarbons (about 78%) until C17 for bio-oils derived from Macauba pulp oils and until C21 from crambe, with similar composition to diesel from 75 to 92%, the bio-oils derived from magnesium soaps were that possessed the highest fraction of diesel. Furthermore, some physico-chemical properties were obtained for bio-oils, such as appearance, color, density, kinematic viscosity and sulfur content and compared with ANP specifications for diesel fuel. The oxygenated compounds identified were ketones, aldehydes, carboxylic acids, ester and alcohols. The bio-oils derived from pyrolysis of crambe oil soaps showed the lowest level of ketones (between 8 and 10%). Furthermore, the solid product was identified by x-ray diffraction (XRD), the composition resulted in carbonates by sodium and barium soaps, and oxides by magnesium soaps.